The impact of trading activity on volatility transmission and interdependence among agricultural commodity markets - Phattanan Boonyanuphong (2018)
© 2014 by the Mathematical Association of Thailand. All rights reserved. This paper aims at studying the volatility and dependence structure among the main agricultural commodity markets. It also investigates the impact of the trading activity of agricultural commodities and the ethanol listing on the volatility transmission for the corn, soybean, and wheat markets. The C– and D–vine copula based GARCH model was used to explain the interdependence of corn, soybean, and wheat prices. We discovered that the listing of ethanol and the trading activity had an impact on the price volatility of corn, soybean, and wheat. The results support the argument that the roles of financialization and of the biofuel increase volatility in the agricultural commodity markets. Moreover, the dependencies between the corn and the wheat returns, and between the corn and the soybean returns have significant variability over time and have higher variations of dependence with symmetrical tail dependences. The higher dynamic dependence and symmetric tail dependence indicate that opportunities to use the related agricultural commodities for portfolio diversification are reduced, particularly during a downturn in the markets.